Assessing Potentiality of Underground Coal Gasification for the Coalfields of Bangladesh - Wae-hayee, Makatar; Kumar Biswas, Arup; Techato, Kuaanan; Phoungthong, Khamphe; Mohideen Batcha, Mohd Faizal (International Journal of Integrated Engineering, 2024)
Underground coal gasification (UCG) can be a viable unconventional coal mining method for long-sought mining solution for the coalfields of Bangladesh, while conventional mining techniques (i.e., underground or opencast) have been disputed for decades. However, there is essentially no work done on UCG potentiality analysis considering the properties of all the coalfields collectively based on the worldwide experiences. To increase a better understanding of UCG prospect identification of Coalfields of Bangladesh, this study is therefore of interest. The study explores the essential factors required to assess the potentiality of 5 Coalfields of Bangladesh for UCG application. The quantification of threshold values was retrieved from published data of known trials occurred around the world. These were then compared with the available data of Coalfields of Bangladesh. In terms of the UCG prospects, all the coalfields passed the depth, thickness, ash content and rank factors to a significant extent. But faulting, overburden or aquifer proximity are somewhat critical for all the coalfields except Jamalganj. This work can help initiating further steps through the analogous approach for siting the first UCG trial in Bangladesh.